Pengaruh SUNO AI (Artificial Intelligence) Terhadap Hasil Belajar Kognitif Peserta Didik Pada Pembelajaran Biologi Materi Klasifikasi Makhluk Hidup Fase E SMA - auliaputri, rasti; Yogica, Relsas (Al-Alam: Islamic Science Education Journal, 2025)
This study aimed to examine the effect of using SUNO AI as a music-based learning medium on students’ cognitive learning outcomes in the topic of biological classification. The research employed a quasi-experimental method with a Randomized Control Group Posttest Only Design, involving two grade X classes at SMA Negeri 1 Baso, namely X E2 as the experimental class and X E4 as the control class. The instrument used was a multiple-choice test consisting of 20 items with a maximum score of 100. The findings revealed that the average posttest score of the experimental class was 75.5, higher than the control class which scored 56.9. These results indicate that SUNO AI can enhance students’ concentration, memory, motivation, and understanding of biological concepts, in line with various learning theories that emphasize the effectiveness of music-based media in supporting the learning process.